Ilokusi yang Memberikan Efek Humor kepada Pembaca dalam Manga Azumanga Daioh - Febryan Ariefandi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2018)
The purpose of this study is to describe the form and meaning of illocutionary acts which create humor effect in the manga entitled Azumanga Daioh Volume 1 by Azuma Kiyohiko. The data source of this study is the castsâ€™ speeches which have potential to be an illocutionary acts. Data were collected and analyzed based on theory of Searle illocutionary acts. Data were also analyzed using theory of Grice cooperative principle to find a maxim of cooperative principleâ€™s violation. The type of this study is qualitative description with pragmatic approach. The result of this study showed that illocutionary acts within Azumanga Daioh Volume 1 categorized at five illocutionary forms, consisted of assertive â€œadmittingâ€, â€œclaimingâ€, and â€œspeculatingâ€, directive â€œrequirementâ€ and â€œprohibitionâ€, expressive â€œcriticismsâ€, comissiveâ€œofferingâ€, and declarative â€œdecidingâ€. Those illocutionary acts also violated maxim of cooperative principles that are maxim of quantity, maxim of quantity, maxim of relevance, and maxim of manner. Illocutionary acts are also acts as a support to create humor within speeches.Â Keywords : Speech Acts, Illocutionary Acts, Cooperative Principle, Violation, Humor